Improving Elementary School Teachers’ English Competence: Challenges, Strategies, and Implementation of Communication-Based Learning - Hasib, Mujib; Pratiwi, Suciaty (Journal of Universal Community Empowerment Provision, 2025)
The main goal of this community service program targets the enhancement of English language abilities among Pinrang Regency’s elementary school teaching staff through training methods based on communication. Intensive one-week training under this program implements practice-focused training methods through storytelling sessions, role-play activities and digital media applications. The program conducts a competence evaluation for teachers before implementing training programs meant to enhance their speech proficiency and interactive English teaching techniques. The training data reveals higher English usage motivation and consciousness among teachers yet multiple learning execution obstacles persist. Three key challenges emerge from teachers’ restricted language skills and insufficient social contact with the English language and their lack of practical experience with classroom interactive teaching methods. The utilization obstacles of technology along with lack of support within the professional community work as important factors which diminish the effectiveness of this training approach. A lasting solution is necessary to enhance the English teaching capabilities of elementary teachers according to the findings of this program. Follow-up sessions and mentoring along with developing a professional community need to support the delivery of effective teaching methods which start from short-term training. Bilingual pedagogy strategies enable teachers to implement English gradually during their lessons. Participation from different organizations would enable improved English teaching quality at elementary schools to operate at its best potential.